Female reproduction neuroendocrinology. Mechanism of action of reproductive hormones. - Coyotupa, Juan (2015)
Blood circulating hormones influence the functional and morphogenetic states of tissues that are distant from the endocrine gland. Many cells are exposed to hormones; however, only few respond. As regards the hypothalamic-pituitary-gonadal axis, we describe the interaction of hormones with their respective effector organ.